ASSESSMENT OF ENVIRONMENTAL RISKS TAKING INTO ACCOUNT THE ASSIMILATION POTENTIAL OF TERRITORIES - Kosharna, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The analysis of materials which describe methodologies of calculation of ecological risks and estimation of assimilatory potential of different natural environments was conducted. Research is concentrated on an identification and substantiation of interrelations between these indexes of the state of territories, and possibilities of improvement of separate methodologies of calculation of ecological risks by applying assimilatory potential. Environment and economic indexes of territories, used in calculations show expediency of continuation of works on perfection of methodologies of calculation of pollution damage (geological environment and other natural environments). Dependences with a new key component, can help maintain ecological safety of territories when extracting mineral resources and substantially influence all system of planning and implementation of geologic works. The obtained results give hope, that quantitative estimation of ecological risks taking into account assimilatory potential of territories will facilitate simplification of prognosis of ecological damage when planning the mineral resources extraction.